Exploring the Structural Diversity in Inhibitors of α-Synuclein Amyloidogenic Folding, Aggregation, and Neurotoxicity - Das, Sukanya; Pukala, Tara L.; Smid, Scott D. (Frontiers in Chemistry, 2018)
Aggregation of α-Synuclein (αS) protein to amyloid fibrils is a neuropathological hallmark of Parkinson’s disease (PD). Growing evidence suggests that extracellular αS aggregation plays a pivotal role in neurodegeneration found in PD in addition to the intracellular αS aggregates in Lewy bodies (LB). Here, we identified and compared a diverse set of molecules capable of mitigating protein aggregation and exogenous toxicity of αSA53T, a more aggregation-prone αS mutant found in familial PD. For the first time, we investigated the αS anti-amyloid activity of semi-synthetic flavonoid 2', 3', 4' trihydroxyflavone or 2-D08, which was compared with natural flavones myricetin and transilitin, as well as such structurally diverse polyphenols as honokiol and punicalagin. Additionally, two novel synthetic compounds with a dibenzyl imidazolidine scaffold, Compound 1 and Compound 2, were also investigated as they exhibited favourable binding with αSA53T. All seven compounds inhibited αSA53T aggregation as demonstrated by Thioflavin T fluorescence assays, with modified fibril morphology observed by transmission electron microscopy. Ion mobility-mass spectrometry (IM-MS) was used to monitor the structural conversion of native αSA53T into amyloidogenic conformations and all seven compounds preserved the native unfolded conformations of αSA53T following 48 hrs incubation. The presence of each test compound in a 1:2 molar ratio was also shown to inhibit the neurotoxicity of preincubated αSA53T using phaeochromocytoma (PC12) cell viability assays. Among the seven tested compounds 2-D08, honokiol and the synthetic Compound 2 demonstrated the highest inhibition of aggregation, coupled with neuroprotection from preincubated αSA53T in vitro. Molecular docking predicted that all compounds bound near the lysine-rich region of the N-terminus of αSA53T, where the flavonoids and honokiol predominantly interacted with Lys 23. Overall, these findings highlight that i) restricted vicinal trihydroxylation in the flavone B-ring is more effective in stabilizing the native αS conformations, thus blocking amyloidogenic aggregation, than dihydroxylation in both A and B-ring, and ii) honokiol, punicalagin and the synthetic imidazolidine Compound 2 also inhibit αS amyloidogenic aggregation by stabilizing its native conformations. This diverse set of molecules acting on a singular pathological target with predicted binding to αSA53T in the folding-prone N-terminal region may contribute towards novel drug-design for PD.